Comparative assessment of clinical rating scales in Wilson’s disease - Volpert, Hanna Maria; Pfeiffenberger, Jan; Gröner, Jan; Stremmel, Wolfgang; Gotthardt, Daniel; Schäfer, Mark; Weiss, Karl Heinz; Weiler, Markus (BMC neurology, 2017)
Wilson’s disease (WD) is an autosomal recessive disorder of copper metabolism resulting in multifaceted neurological, hepatic, and psychiatric symptoms. The objective of the study was to comparatively assess two clinical rating scales for WD, the Unified Wilson’s Disease Rating Scale (UWDRS) and the Global Assessment Scale for Wilson’s disease (GAS for WD), and to test the feasibility of the patient reported part of the UWDRS neurological subscale (termed the “minimal UWDRS”).